Strengthening MSME Creditworthiness through Financial Transparency and Digital Accounting Innovation - Faizal Rizky Yuttama; Yadi Fakhruzein Terang Jaya (Green Inflation: International Journal of Management and Strategic Business Leadership, 2025)
Limited access to formal financing remains a persistent challenge for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, despite their vital contribution to economic development. Among the key barriers are poor-quality financial reporting and the lack of digital accounting adoption, which hinder financial transparency and lender trust. This study aims to analyze the influence of financial reporting quality and the use of digital accounting technology on MSMEs’ access to financing from formal financial institutions. A quantitative explanatory research design was employed, involving 120 MSMEs in Banyumas Regency, Indonesia. Primary data were collected through structured questionnaires and analyzed using multiple linear regression after satisfying classical assumption tests. The results indicate that both financial reporting quality and digital accounting technology have significant positive effects on access to financing. Financial reporting quality exhibited a slightly stronger influence, confirming its role in reducing information asymmetry and signaling creditworthiness. The adoption of digital accounting tools, such as BukuKas and Accurate, improved financial documentation, auditability, and lender confidence. These findings underscore that internal financial practices are critical enablers of financial inclusion, especially in semi-urban contexts.The study concludes that enhancing the quality of financial reports and promoting digital accounting adoption are essential strategies for improving MSMEs’ access to external funding. The findings offer practical implications for policymakers and financial institutions while also contributing to the theoretical understanding of MSME financial behavior in the digital era.